Pregnant Dutch Women Have Inadequate Iodine Status and Selenium Intake - Mayunga, K. Clara; Lim-A-Po, Melany; Lubberts, Janniek; Stoutjesdijk, Eline; Touw, Daan J.; Muskiet, Frits A. J.; Dijck-Brouwer, D. A. Janneke (Nutrients, 2022)
Iodine and selenium are essential for thyroid hormone synthesis. Iodine and selenium interact. Pregnancy increases the maternal iodine requirement. We previously reported inadequate iodine status in pregnant Dutch women. Since little is known about their selenium intake, we investigated the iodine status and selenium intake in relation to iodine and selenium supplement use during pregnancy. Iodine status was established in 201 apparently healthy pregnant women as 24 h iodine excretion (24H-UIE; sufficient if median ≥225 µg), iodine concentration (24H-UIC; ≥150 µg/L) and iodine/creatinine ratio (24H-UICR; ≥150 µg/g). Selenium intake was calculated from 24 h selenium excretion. Iodine status in pregnancy proved insufficient (medians: 24H-UIE 185 µg; 24H-UIC 95 µg/L; 24H-UICR 141 µg/g). Only women taking 150 µg iodine/day were sufficient (median 24H-UIE 244 µg). Selenium intake was below the Estimated Average Requirement (EAR; 49 µg/day) in 53.8%, below the Recommended Dietary Allowance (RDA; 60 µg/day) in 77.4% and below the Adequate Intake (AI; 70 µg/day) in 88.7%. Combined inadequate iodine status and selenium intake <RDA was found in 61%. Women who want to become pregnant should, consistently with WHO and ETA recommendations, be advised to use a 150 µg iodine-containing supplement. Concomitant selenium supplementation should be added to this advice, at least in The Netherlands.